Pesticide handling and human health: Conventional and organic cotton farming in Benin - Ghislain B. D. Aïhounton; Arne Henningsen; Neda Trifkovic (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2021)
Synthetic pesticides can be detrimental to the health of humans, particularly when handled inappropriately, which is often the case in developing countries. We investigate to what extent using personal protective equipment (PPE) during pesticide application can mitigate the detrimental health effects of pesticides. Our empirical analysis is based on data from smallholder cotton farmers in Benin and includes both conventional cotton farmers who extensively use synthetic pesticides and organic cotton farmers who are only allowed to use bio-pesticides. Using per-capita health expenditure as proxy for the health of the farmers, our results show that conventional cotton farmers generally have significantly poorer health than organic cotton farmers because most conventional farmers wear insufficient PPE when spraying pesticides. While PPE use vastly improves the health of conventional farmers, we do not find a statistically significant effect on the health of organic cotton farmers, which could indicate that bio-pesticides have much smaller detrimental health effects than synthetic pesticides. However, conventional farmers have a similar state of health as organic farmers when they use four or more PPE items. Hence, measures that encourage conventional cotton farmers to use more PPE during pesticide spraying or to adopt organic farming would substantially improve these farmers' health.
Keywords: I12; I15; J28; O13; Q12; Q56; 330; pesticides; protective equipment; health; organic farming; smallholder farmers; cotton; Africa